Playfair : everybody's guide to noncompetitive play - Weinstein, Matt.; Goodman, Joel ([Place of publication not identifed] : [publisher not identified], 1980)
This is a book about games for people who are interested in learning about a new type of play that lets people be supportive and cooperative and open with each other.
Includes index.
Keywords: GAMES